2015
DOI: 10.1007/s00044-015-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a library of 4-aryl/heteroaryl-4H-fused pyrans for xanthine oxidase inhibition: synthesis, biological evaluation and docking studies

Abstract: A series of 4-aryl/heteroaryl-4H-fused pyrans was synthesized via multicomponent reaction in a microwave synthesizer. All the pyrans were evaluated for in vitro xanthine oxidase inhibition. Structure-activity relationship was also established. Among the series of 108 compounds, Compound 5n was the most potent displaying remarkable inhibition against the enzyme with an IC 50 value of 0.59 lM. Enzyme kinetic study was carried out for the compound 5n to determine the type of inhibition. The study revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…The pyran motif was also investigated by Nepali and colleagues with eight different libraries of compounds 197 – 204 . More than 100 compounds were synthesized and tested for inhibitory activity against XO at a concentration of 50 μ m .…”
Section: Non‐purine‐like Inhibitors Of Xomentioning
confidence: 99%
See 1 more Smart Citation
“…The pyran motif was also investigated by Nepali and colleagues with eight different libraries of compounds 197 – 204 . More than 100 compounds were synthesized and tested for inhibitory activity against XO at a concentration of 50 μ m .…”
Section: Non‐purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…The R enantiomer of compound 196 was also found by molecular docking studies to fit better in the active site of the enzymethan its S enantiomer. The pyran motif wasa lso investigated by Nepali and colleagues [137] with eight different libraries of compounds 197-204.M ore than 100 compounds were synthesized and tested for inhibitory activity against XO at a concentration of 50 mm.O nly those compounds with more than 80 %i nhibitionw ere studied further.Atotal of 41 com-pounds met this condition, and werem easured to have IC 50 valuesr anging from 34.3 mm down to 0.59 mm for compound 205 (compared to allopurinol with IC 50 = 8.29 mm). SAR studies suggested that ah alogeno rn itro group was preferred over methoxy or hydroxy group as as ubstituent on the phenyl ring.…”
Section: Other Miscellaneous Compoundsmentioning
confidence: 99%
“…The biological data (IC 50 ) of 4-aryl/ heteroaryl-4H-fused pyrans (Table 1) included in this study were obtained from literature 26 . IC 50 denotes the concentration of the test compound that exerts 50% inhibition of the biological action.…”
Section: Data Collectionmentioning
confidence: 99%
“…Recently, a series of forty-one 4-aryl/ heteroaryl-4H-fused pyrans, has been prepared and tested for xanthine oxidase (XO) inhibition 26 . This family of compounds offers great opportunity to identify the relevant properties inherent in these compounds that dictate their xanthine oxidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pyranochromenone compounds have long been known to manifest a wide range of pharmaceutical properties, for instance, they exhibit anticancer, anti‐HIV, analgesic, anti‐inflammatory, anti‐TB, antifungal and cytotoxic activities (Figure ). Pyranochromenone derivatives act as xanthine oxidase inhibitor and also treat some neurodegenerative disorders, viz; Parkinson's disease, Alzheimer's disease and amyotrophic lateral sclerosis. Their existence in natural products is also significant ,…”
Section: Introductionmentioning
confidence: 99%